The Clinical and Genetic Spectrum of 82 Patients With RAG Deficiency Including a c.256_257delAA Founder Variant in Slavic Countries - Sharapova, Svetlana O.; Skomska-Pawliszak, Małgorzata; Rodina, Yulia A.; Wolska-Kuśnierz, Beata; Dabrowska-Leonik, Nel; Mikołuć, Bozena; Pashchenko, Olga E.; Pasic, Srdjan; Freiberger, Tomáš; Milota, Tomáš; Formánková, Renata; Szaflarska, Anna; et al. (Frontiers in Immunology, 2020)
BACKGROUND. Variants in recombination-activating genes (RAG) are common genetic causes of autosomal recessive forms of combined immunodeficiencies (CID) ranging from severe combined immunodeficiency (SCID), Omenn syndrome (OS), leaky SCID and CID with granulomas and/or autoimmunity (CID-G/AI) and even milder presentation with antibody deficiency. OBJECTIVE. We aim to estimate the incidence, clinical presentation, genetic variability and treatment outcome with geographic distribution of patients with the RAG defects in populations inhabiting South, West and East Slavic countries. METHODS. Demographic, clinical and laboratory data were collected from RAG deficient patients of Slavic origin via chart review, retrospectively. Recombinase activity was determined in vitro by flow cytometry-based assay. RESULTS. Based on the clinical and immunologic phenotype, our cohort of 82 patients from 68 families represented a wide spectrum of RAG deficiencies, including SCID (n=20), OS (n=37) and LS/CID (n=25) phenotypes. Sixty-seven (81.7%) patients carried RAG1 and 15 patients (18.3%) carried RAG2 biallelic variants. We estimate that the minimal annual incidence of RAG deficiency in Slavic countries varies between 1 in 180,000 – 300,000 live birth and it may vary secondary to health care disparities in these regions. In our cohort, 70% (n=47) of patients with RAG1 variants carried p.K86VfsTer33 (c.256_257delAA) allele, either in homozygous (n=18, 27%) or compound heterozygous (n=29,43%) form. The majority (77%) of patients with homozygous RAG1 p.K86VfsTer33 variant originated from Vistula watershed area in Central and Eastern Poland, and compound heterozygote cases distributed among all Slavic countries except Bulgaria. Clinical and immunological presentation of homozygous RAG1 p.K86fsTer33 cases was highly diverse (SCID, OS, AS/CID) suggestive of strong influence of additional genetic and/or epigenetic factors in shaping the final phenotype. CONCLUSION. We propose that RAG1 p.K86VfsTer33 is a founder variant originating from the Vistula watershed region in Poland, which may explain a high proportion of homozygous cases from Central and Eastern Poland and the presence of the variant in all Slavs. Our studies in this cohort of RAG1 founder variants confirm that clinical and immunological phenotype only partially depend on the underlying genetic defect. As access to HSCT is improving among RAG deficient patients in Eastern Europe, we anticipate improvements in survival.